2019
DOI: 10.1097/scs.0000000000005631
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Discomfort and Injury in Craniofacial and Maxillofacial Surgeons

Abstract: Introduction: Long, complex surgical procedures with non-ergonomic postures, headlights, loupe magnification, and microscope use may put craniofacial and maxillofacial surgeons at an increased risk of work-related musculoskeletal discomfort (WRMD). Identifying the prevalence and impact of WRMD may guide preventive strategies to prolong well-being, job satisfaction, and career duration. Methods: A 31-question survey was designed to evaluate WRMD. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
1
17
0
3
Order By: Relevance
“…Further, the limited research we identified on the gender effects of hand mechanics indicates significant differences in force generation between male and female hands [13]. Multiple fields of surgery, including adult reconstructive surgery and spine surgery within orthopedics, have begun to acknowledge the toll poor ergonomics and work-related injuries can take on surgeons' careers and their overall health and well-being [14][15][16][17][18][19]. Despite the fact we did not find significant correlations between surgeon glove size and surgeon height with the likelihood of physical symptoms, we believe that the ergonomic use of surgical instruments is multifactorial and may include factors such as grip strength and hand structure and mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the limited research we identified on the gender effects of hand mechanics indicates significant differences in force generation between male and female hands [13]. Multiple fields of surgery, including adult reconstructive surgery and spine surgery within orthopedics, have begun to acknowledge the toll poor ergonomics and work-related injuries can take on surgeons' careers and their overall health and well-being [14][15][16][17][18][19]. Despite the fact we did not find significant correlations between surgeon glove size and surgeon height with the likelihood of physical symptoms, we believe that the ergonomic use of surgical instruments is multifactorial and may include factors such as grip strength and hand structure and mechanics.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 , 20 Moreover, although use of a surgical headlight is recommended for proper illumination of the surgical field, 3 the weight of the headlight, along with loupes, can increase the load on the neck, leading to the risk of muscular discomfort and fatigue. 6 In contrast, the microscope’s built-in light eliminates the need for a headlight and thus any added strain on the neck and body.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil scoping review pengaruh lama dan posisi kerja terhadap keluhan muskuloskeletal pada petugas medis dapat dilihat pada Tabel. [4][5][6][7][8][9][11][12][13][14][15][16][17] Hasil review artikel yang diperoleh dari negara di Benua Amerika didapatkan 4 artikel dari Amerika Serikat dan 1 artikel dari Brazil; untuk Benua Asia didapatkan 4 artikel dari India, 2 artikel dari Iran, dan 1 artikel dari Hong Kong; serta untuk Benua Afrika didapatkan 1 artikel dari Mesir. Ketiga belas artikel yang diperoleh semua menggunakan studi penelitian kualitatif.…”
Section: Hasilunclassified
“…Hasil penelitian yang dilakukan oleh Howarth dkk. 15 pada 95 responden ahli bedah yang melakukan prosedur craniofacial and maxillofacial surgeons melaporkan bahwa rasa ketidaknyamanan pada tubuh dipengaruhi oleh postur tubuh. Mempertahankan postur leher yang tertekuk saat melakukan prosedur di ruang operasi juga berkontribusi dalam timbulnya nyeri.…”
Section: Pembahasanunclassified